An Analysis of the Structure, Validity, and Reliability of the Collegian Attitudes Toward Inclusive Campus Recreation (CAICR) Scale. Issue 2 (October 2019) - McKay, Cathy; Park, Jung Yeon; Haegele, Justin
The purpose of this study was to test the construct validity and internal consistency of the Collegian Attitudes toward Inclusive Campus Recreation (CAICR) Scale, a collegiate adaptation of the Children's Attitudes toward Integrated Physical Education–Revised Scale. The CAICR seeks to measure attitudes toward inclusive lifetime fitness, sport, and recreation at the collegiate level. Participants were 192 college students. The factor structure of the scale was investigated using a confirmatory factor analysis with the weighted least square estimator. The CAICR Scale demonstrated acceptable internal consistency levels for the complete scale (11 items), inclusion subscale (6 items), and sport modification subscale (5 items). Results suggest that the 2-factor model (indicating inclusion and sport modification) showed suitable model fit, and the model outperformed a single-factor solution. Current findings suggest that the CAICR has the ability to contribute to sociocultural attitude research at the collegiate level in a valid and reliable manner.